(untitled) (Physical Education, Health and Social Sciences, 2025)
Cholelithiasis, or gallstone disease, is one of the most prevalent gastrointestinal disorders worldwide, often remaining asymptomatic but carrying risks of complications such as acute cholecystitis and gallstone pancreatitis. In Pakistan, limited data exist on its prevalence and risk factors in the Peshawar region. To determine the prevalence of cholelithiasis and identify its associated risk factors among adult patients undergoing abdominal ultrasonography in a tertiary care hospital in Peshawar, Pakistan. A hospital based cross sectional study was conducted from January to August 2025 at Northwest General Hospital, Peshawar. Using convenience sampling, 368 patients aged ≥17 years undergoing abdominal ultrasonography were recruited. Data on sociodemographic characteristics and gallstone presence were confirmed through ultrasound examination. Statistical analysis was performed using SPSS v. 25. Of 368 participants (49.7% male, 50.3% female; age 17-96 years), 35 (9.5%) were diagnosed with cholelithiasis, showing slight female predominance (51.4% vs 48.6%). Peak prevalence occurred in the 37-56 years age group. Significant risk factors included marital status (100% of cases), physical inactivity (54.3%), recent weight loss (45.7%), positive family history (42.9%), and diabetes mellitus (34.3%). Lesser associations were found with obesity (20.0%), smoking (8.6%), liver disease (5.7%), and contraceptive use (2.9%). Cholelithiasis prevalence was 9.5% in this population, predominantly affecting married individuals and those aged 37-56 years. Physical inactivity, weight loss, family history, and diabetes mellitus were identified as major risk factors, while obesity, smoking, liver disease, and contraceptive pills also showed some contribution to cholelithiasis development.